Effects of Albedo Addition on Pomegranate Juice Physicochemical, Volatile and Chemical Markers - Vázquez-Araújo, Laura; Chambers, Edgar, IV; Carbonell-Barrachina, Ángel A. (My University, 2015)
Five commercial juices, representing the five clusters of this juice, were characterized before and after maceration with 10% pomegranate albedo (control- and albedo treated (AT)-juices, respectively). Commercial juices were macerated with albedo homogenate for 24 h, and then the albedo was removed. Total soluble solids, titratable acidity, maturity index (MI), total phenolic content (TPC), volatile composition, and flavor profile were evaluate in control- and AT-juices. From all physico-chemical characteristics, only the TPC was significantly affected by the treatment and ranged from 846 to 3784 mg gallic acid L−1 and from 2163 to 5072 mg gallic acid L−1 in control- and AT-juices, respectively; the increment in TPC was more than 1.3-fold in all AT-juices. No clear pattern was found when studying the volatile composition; only significant increases were observed in the contents of hexanal, 2-hexenal, and 3-hexenal in all AT-samples. The flavor profile study indicated that three of the five samples increased their bitterness and/or astringency. In addition, new attributes, which were not present in the control juices, appeared after maceration with albedo in some samples: green-bean, brown-sweet, and green-viney. This information will be useful in developing and promoting new “healthy” products based on pomegranate.
Citation: Vázquez-Araújo, L., Iv, E. C., & Carbonell-Barrachina, Á. A. (2015). Effects of Albedo Addition on Pomegranate Juice Physicochemical, Volatile and Chemical Markers. Beverages, 1(1), 17–33. https://doi.org/10.3390/beverages1010017
Keywords: Punica Granatum.; Flavor; Phenolic Content; Spme-Gcms; Volatile Compounds